Carbon Dioxide Exchanges in Leaves. I. Discrimination Between (14)CO(2) and (12)CO(2) in Photosynthesis - Yemm, E. W. (1969)
In order to measure CO(2) exchange reactions by leaves using isotopes of CO(2), it is necessary to know precisely the discrimination against (14)CO(2) by leaves. Earlier determinations of discrimination are at variance, and may be inaccurate because of assumptions made about the rate of photorespiration. Maize leaves evolve little or no CO(2) in light, and so provide suitable material for this measurement. Discrimination against (14)CO(2) in photosynthesis by maize leaves is almost precisely the same as in CO(2) absorption by NaOH solution, amounting to 2.1 and 2.0% respectively. The agreement between these values and their close approximation to the relative rates of diffusion of (12)CO(2) and (14)CO(2), calculated from Graham's law, shows that diffusion into the leaf is primarily responsible for discrimination against (14)CO(2) in photosynthesis.